Techno-economic assessment of sugarcane bagasse pith-based briquette production and performance analysis of briquette feed gasifier-engine system - Raj R.; Tirkey J.V. (My University, 2025)
Utilizing agriculture co-products and agricultural residues directly leads to Energy, Economic, and Environmental sustainability. Sugar production industries produce a considerable amount of sugarcane bagasse (SB) as a co-product, whereas SB is used in paper-mill sectors, which have a large amount of waste as sugarcane bagasse pith (SBP). In this view, the novelty of the present study aims to ensure the economic viability of the SBP briquette production plant, after that, briquette-based producer gas (PG) generation and application to compression ignition (CI) engine for diesel substitution. The economic analysis includes the Net Present Value (NPV) and Profitability Index (PI) for the feasibility check. And gasifier-engine analysis includes the effect of gasification equivalence ratio (GER), engine compression ratio (CR), and load on engine brake thermal efficiency (BTE), diesel saving, Sound, Exhaust gas temperature (EGT), and emissions (CO, HC, CO2, NOx). Further, operating variables were optimized with the desirability approach of Response surface methodology (RSM). In the result, NPV and PI values were found to be Rs 49,64,379.5 (≈0.06 million USD) and 1.98, respectively. However, the economic feasibility of the plant is sensitive to capital cost, briquette market price, and discount percentages. Regarding gasifier-engine performance, the maximum diesel substitution was found to be 66.15% at dual fuel (DF) mode engine run. RSM-based optimization result showed the optimum operating setting of 0.10 GER, 16 CR, and 9.93 kg load at 1500 rpm with a composite desirability of 0.798. Accordingly, at optimal input parameters, the magnitudes of engine performance as BTE, Sound, CO, HC, CO2, and NOx were found to be 27.18%, 91.21 db, 0.10%vol., 53.19 ppm, 2.33%vol., and 8.43 ppm respectively. Thus, the higher value of the economic index and substantial amount of diesel fuel saving through the gasifier-engine system ensures the economic feasibility of briquetting and power generation technology. © 2023 Elsevier Ltd